Analysis Transfer of the Function Cover of Agricultural Land Become a Housing Area and Industry in the Semarang City with Approach of Remote Sensing and Geographic Information System - Harnawan Nurul Asna; Frederik Samuel Papilaya (Journal of Applied Geospatial Information, 2019)
The purpose of this study was to find out how much area of agricultural land was converted because of the high property business activities in Semarang City, the data used for this study were taken from 1999 to 2018. The classification method used in this study was the remote sensing method using the unsupervised classification technique. Output of this study is the extensive data of agricultural land cover change obtained from 1999 to 2018. The results of this study can prove that the Geographic Information System can be used to find out how much agricultural land cover change in Semarang City from 1999 to 2018. The area of agricultural land that has been converted is from 1999 to 2009 around 3072 ha and from 2009 to 2018 around 1071.4 ha.